Calon Independery Kualitas Pilkada dan Pelembagaan Parpol - - Pratikno (Jurnal Ilmu Sosial dan Ilmu Politik, 2007)
Direct elections of the regional head of 2005-2006 were widely criticized due to the persistence of money politics practices and elites dominance in the electoral processes. To minimize the problems, there are strong pressures to open opportunity for independent candidates to provide an alternative for the party proposed candidates. This article argues that the possible impact of independent candidacy for reforming electoral processes and democratizing political party institution will be very limited. Deeply rooted internal conflicts and pragmatic coalition between political parties will be significant constraints for reform. Initiation of independent candidate will be meaningless unless to be integrated into a wider electoral and party reform.